Historiografía y regiones en Argentina. Desarrollo, balance y perspectivas - María Silvia Leoni (Bulletin de l'Institut Français d'Études Andines, 2018)
This article analyzes the link between regional history and the construction of regions in Argentina from the end of the 19th century to the present, identifying their different moments and providing an assessment of their current situation. The construction processes of sub-national regions will be studied in relation to the construction of the national state, to the inventions and transformations of identities, to memory production and to the emergence and development of regional studies in these contexts.